Pulp Sheet

A pulp sheet with oxidized pulp treated by TEMPO catalyst achieves enhanced wet strength by controlling surface aldehyde groups, addressing the limitations of conventional agents and achieving superior wet strength without additional chemicals.

JP7608713B2Active Publication Date: 2025-01-07OJI HLDG CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2019142292
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-08-01
Publication Date
2025-01-07
Estimated Expiration
2039-08-01

AI Technical Summary

Technical Problem

Existing pulp sheets with wet paper strength and high tightness do not achieve sufficient wet paper strength enhancement, and the use of conventional wet paper strength agents like PAE, PVAm, and dextran aldehyde face issues such as chemical stability, production costs, and regulatory constraints.

Method used

A pulp sheet containing oxidized pulp treated with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst, with specific surface aldehyde group and carboxy group contents, and average fiber length and diameter, enhancing interfiber strength through hemiacetal bond formation without the need for additional wet paper strength agents.

Benefits of technology

The pulp sheet achieves excellent wet strength and can reduce or eliminate the use of wet paper strength agents, improving wet strength while avoiding chemical stability and regulatory issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608713000003
    Figure 0007608713000003
  • Figure 0007608713000001
    Figure 0007608713000001
  • Figure 0007608713000002
    Figure 0007608713000002
Patent Text Reader

Abstract

To provide a pulp sheet excellent in wet strength.SOLUTION: A pulp sheet of this invention contains an oxidized pulp. The oxidized pulp is a pulp oxidized with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst, and the amount of surface aldehyde group of the oxidized pulp is 0.010 mmol / g or more and 0.25 mmol / g or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pulp sheet. [Background technology]

[0002] Traditionally, polyamide epichlorohydrin resin (PAE) has been used as a chemical to impart wet strength to paper. PAE has a wide range of applications and is widely used because it exhibits good wet strength over a wide pH range. Other wet strength agents known besides PAE include polyvinylamine (PVAm) and dextran aldehyde. In recent years, a method has been developed in which pulp is oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst to modify the pulp surface and thereby increase wet strength. Patent Document 1 describes a pulp slurry containing oxidized pulp and non-oxidized pulp, in which the content of the oxidized pulp is 20 to 60 mass% based on the total mass of the oxidized pulp and non-oxidized pulp, and the oxidized pulp is pulp oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst, for the purpose of providing a pulp sheet having excellent wet strength and high tightness and suppressed yellowing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-223042 A Summary of the Invention [Problem to be solved by the invention]

[0004] By using the pulp slurry described in Patent Document 1, a pulp sheet having high wet strength and high compactness can be obtained, but the wet strength enhancing effect is not sufficient. An object of the present invention is to provide a pulp sheet having excellent wet strength. [Means for solving the problem]

[0005] The present inventors have found that the above problems can be solved by a pulp sheet containing pulp having a specific amount of surface aldehyde groups and oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst. That is, the present invention provides the following: <1> ~ <5> Regarding. <1> A pulp sheet comprising an oxidized pulp, the oxidized pulp being pulp oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst; The oxidized pulp has a surface aldehyde group content of 0.010 mmol / g or more and 0.25 mmol / g or less. <2> The oxidized pulp has a carboxyl group content of 0.1 mmol / g or more and 1.7 mmol / g or less. <1> The pulp sheet according to claim 1. <3> The average fiber length of the oxidized pulp is 0.1 mm or more and 3.0 mm or less. <1> or <2> The pulp sheet according to claim 1. <4> The average fiber diameter of the oxidized pulp is 10 μm or more and 50 μm or less. <1> ~ <3> 13. The pulp sheet according to claim 12, <5> The content of the oxidized pulp is 65% by mass or more of the total pulp. <1> ~ <4> 13. The pulp sheet according to claim 12, Effect of the Invention

[0006] According to the present invention, a pulp sheet having excellent wet strength can be provided. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a graph showing the relationship between the surface aldehyde group content of the pulp constituting the pulp sheets obtained in the Examples and Comparative Examples and the wet strength of the pulp sheets. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Pulp sheet] The pulp sheet of the present invention is a pulp sheet containing oxidized pulp, the oxidized pulp being pulp oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst, and the amount of surface aldehyde groups of the oxidized pulp is 0.010 mmol / g or more and 0.25 mmol / g or less. According to the present invention, a pulp sheet having excellent wet strength can be obtained. Although the detailed reasons why the above-mentioned effects are obtained are unclear, part of the reason is thought to be as follows. By setting the amount of surface aldehyde groups of the oxidized pulp constituting the pulp sheet within a specific range, hemiacetal bonds are formed between the aldehyde groups and hydroxyl groups on the pulp surface between the fibers of the oxidized pulp, improving the strength between the fibers and thereby improving the wet strength. The inventors' studies have found that for wet strength, it is not the amount of aldehyde groups in the oxidized pulp but the amount of surface aldehyde groups that is important, and that by setting the amount of surface aldehyde groups in the oxidized pulp within a specific range, a pulp sheet with extremely excellent wet strength can be obtained. Conventionally, one method for enhancing wet strength has been to use wet strength agents, but when PAE (polyamide epichlorohydrin resin) is used as a wet strength agent, there is a problem that low molecular weight chlorine organic compounds (AOX), which are regulated substances, are generated during the production of pulp sheets, and there is a demand for pulp sheets that can exhibit good wet strength without using PAE. Also, when PVAm (polyvinylamine) or dextran aldehyde is used as a wet strength agent, there are problems in terms of production costs and chemical stability, respectively, and their use has not progressed. According to the present invention, a pulp sheet having excellent wet strength can be obtained using only pulp fibers, so that a pulp sheet having excellent wet strength can be obtained even if the amount of wet strength agent used is reduced or even if no wet strength agent is used. The present invention will now be described in further detail.

[0009] <Oxidized pulp> The pulp sheet of the present invention contains oxidized pulp, which is pulp oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst (TEMPO-oxidized pulp). In TEMPO-oxidized pulp, the hydroxyl group at the C6 position of glucose is easily oxidized. In the present invention, "oxidized pulp" refers to pulp that has been oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst, in which 10% or more of the hydroxyl groups at the C6 position of the total glucose units that are the constituent units of the pulp have been oxidized, and the amount of surface aldehyde groups is 0.010 mmol / g or more and 0.25 mmol / g or less.

[0010] In the present invention, the amount of surface aldehyde groups on the oxidized pulp is 0.010 mmol / g or more, preferably 0.012 mmol / g or more, more preferably 0.014 mmol / g or more, and even more preferably 0.016 mmol / g or more, from the viewpoint of improving the wet strength of the pulp sheet, and is 0.25 mmol / g or less, preferably 0.15 mmol / g or less, more preferably 0.05 mmol / g or less, and even more preferably 0.03 mmol / g or less, from the viewpoint of production. The amount of surface aldehyde groups of the oxidized pulp is measured by the method described in the Examples.

[0011] Although there is no particular limitation on the method for adjusting the amount of surface aldehyde groups of the oxidized pulp to the above range, it is possible to increase the amount of surface aldehyde groups on the surface of the oxidized pulp by beating treatment. Therefore, it is possible to adjust the amount of surface aldehyde groups by (1) adjusting the total amount of carboxy groups of the oxidized pulp to a specific range and (2) carrying out an appropriate beating treatment. The carboxy group content of the oxidized pulp is preferably 0.1 mmol / g or more, more preferably 0.2 mmol / g or more, and even more preferably 0.3 mmol / g or more, from the viewpoint of making the amount of surface aldehyde groups 0.010 mmol / g or more, and is preferably 1.7 mmol / g or less, more preferably 1.2 mmol / g or less, even more preferably 1.0 mmol / g or less, and particularly preferably 0.9 mmol / g or less, from the viewpoint of suppressing excessive fineness of the pulp in the beating treatment. The above carboxy group content is the total carboxy group content of the oxidized pulp. In addition, the aldehyde group content (total aldehyde group content) of the oxidized pulp is not particularly limited as long as the desired amount of surface aldehyde groups is obtained, but is preferably 0.01 mmol / g or more, more preferably 0.05 mmol / g or more, even more preferably 0.15 mmol / g or more, and is preferably 0.5 mmol / g or less, more preferably 0.35 mmol / g or less, even more preferably 0.25 mmol / g or less. In the TEMPO oxidation, the hydroxyl group at C6 of glucose, a monosaccharide that constitutes cellulose, is oxidized to a carboxyl group via an aldehyde group. Therefore, the aldehyde group content increases from the early stage of the oxidation, but does not increase as the oxidation reaction progresses. The carboxyl group content and the aldehyde group content in the pulp can be measured by conductometric titration. In particular, the amount of aldehyde groups can be calculated from the amount of carboxyl groups before and after oxidation by oxidizing with chlorous acid in an acetate buffer solution. In detail, the amount of aldehyde groups can be measured by the method described in the Examples.

[0012] The degree of beating, when specified according to the method described in TAPPI Test Method T 248 sp-08, is such that the rotation speed of the PFI mill is preferably 100 rpm or more, more preferably 1000 rpm or more, even more preferably 5000 rpm or more, particularly preferably 7000 rpm or more, and is preferably 40000 rpm or less, more preferably 30000 rpm or less, and even more preferably 25000 rpm or less. As the pulp beating machine, for example, a normal pulp beating machine such as a single disc refiner, a double disc refiner, or a conical refiner may be used.

[0013] Oxidized pulp is pulp in which the hydroxyl groups of glucose, the structural unit of pulp, have been oxidized, and is obtained by carrying out an oxidation reaction using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst. As mentioned above, in the TEMPO oxidation treatment, the C6 position of glucose is easily oxidized. As the pulp used as the raw material for the oxidized pulp, it is preferable to use softwood kraft pulp or hardwood kraft pulp. Examples of softwood kraft pulp include unbleached softwood kraft pulp (NUKP), bleached softwood pulp (NBKP), semi-bleached softwood kraft pulp (NSBKP), and softwood sulfite pulp. Examples of hardwood kraft pulp include unbleached hardwood kraft pulp (LUKP), bleached hardwood kraft pulp (LBKP), semi-bleached hardwood kraft pulp (LSBKP), and hardwood sulfite pulp. Among these, at least one selected from bleached softwood kraft pulp (NBKP) and bleached hardwood kraft pulp (LBKP) is preferable. The pulp used may be one type alone or two or more types may be used in combination.

[0014] In addition to softwood kraft pulp and hardwood kraft pulp, the present invention can use various known pulps, such as mechanical pulps such as stone ground pulp (SGP), pressed stone ground pulp (PGW), refiner ground pulp (RGP), thermo ground pulp (TGP), chemi-ground pulp (CGP), groundwood pulp (GP), and thermo mechanical pulp (TMP); disintegrated waste paper pulp produced from brown paper, kraft envelope paper, magazine paper, newspaper paper, flyer paper, office paper, cardboard paper, white paper, Kent paper, imitation waste paper, and land certificate paper; disintegrated and deinked waste paper pulp or disintegrated, deinked, and bleached waste paper pulp; and pulp produced chemically or mechanically from non-wood fibers such as kenaf, hemp, and reed.

[0015] The amount of TEMPO used is not particularly limited as long as it is a catalytic amount capable of promoting the oxidation reaction of pulp. From the viewpoint of appropriately proceeding with the oxidation reaction of pulp, the amount of TEMPO used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the bone dry mass of the pulp to be subjected to the oxidation reaction, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. In the TEMPO oxidation treatment, pulp is oxidized in the presence of an oxidizing agent. Examples of the oxidizing agent include hypochlorous acid, persulfuric acid, hydrogen peroxide, periodic acid, and salts thereof, and among these, hypochlorous acid and its salts are preferred. The amount of hypochlorous acid and its salts added during the oxidation treatment is preferably 1.0 mmol or more, more preferably 1.5 mmol / g or more, and preferably 5.0 mmol or less, more preferably 3.0 mmol / g or less, per 1 g of pulp. The oxidation treatment preferably includes a step of mixing pulp, TEMPO, and an oxidizing agent. In the mixing step, stirring is preferably performed, and the stirring conditions are not particularly limited as long as the components are uniformly mixed. The stirring conditions may be set as desired depending on the type of the reaction vessel and the stirrer. The reaction time of the oxidation reaction is not particularly limited, and the reaction may be performed until the desired total amount of carboxy groups is reached. The amount of oxidizing agent added may be adjusted, and the reaction may be performed until the oxidizing agent used in the reaction is consumed. The consumption of the oxidizing agent can be confirmed by the fact that the pH of the pulp slurry no longer decreases. In addition, the oxidation reaction using TEMPO as a catalyst may be carried out under conditions of a pH of 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be carried out, for example, by adding pulp as a fiber raw material, TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). The TEMPO oxidation treatment may be carried out under conditions of a pH of 10 to 11. This type of treatment is also called alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be carried out, for example, by adding TEMPO as a catalyst, sodium bromide as a co-catalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.

[0016] The method may further include a step of recovering TEMPO after the oxidation treatment. By recovering TEMPO, which is a catalyst used in obtaining oxidized pulp, the cost required for obtaining oxidized pulp can be reduced. In the process of recovering TEMPO, the slurry after the oxidation reaction is filtered and the filtrate is recovered, whereby TEMPO can be recovered. If necessary, the filtrate is concentrated and used in the next process.

[0017] After the oxidation treatment, washing, neutralization, etc. may be performed. The washing is performed by washing the pulp that has been subjected to the TEMPO oxidation treatment with water or an organic solvent. The washing step may be performed after each step described below, and the number of washing steps performed in each washing step is not particularly limited. Between the oxidation treatment and the above-mentioned beating treatment, the pulp that has been subjected to the TEMPO oxidation treatment may be subjected to an alkali treatment (neutralization treatment). The method of the alkali treatment is not particularly limited, but an example of the method is a method in which the pulp that has been subjected to the TEMPO oxidation treatment is immersed in an alkali solution.

[0018] It is preferable to subject the pulp that has been subjected to the TEMPO oxidation treatment to the above-mentioned beating treatment so that the amount of surface aldehyde groups falls within the desired range, and the oxidized pulp used in the present invention can be obtained by the above-mentioned method.

[0019] From the viewpoint of improving wet strength, the average fiber length of the oxidized pulp is preferably 0.1 mm or more, more preferably 0.3 mm or more, and even more preferably 0.5 mm or more, and from the viewpoint of ease of production, it is preferably 5.0 mm or less, more preferably 4.0 mm or less, even more preferably 3.0 mm or less, particularly preferably 2.0 mm or less, and most preferably 1.0 mm or less.

[0020] From the viewpoint of improving wet strength, the average fiber diameter of the oxidized pulp is preferably 10 μm or more, more preferably 12 μm or more, even more preferably 14 μm or more, and is preferably 50 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less.

[0021] <Non-oxidized pulp> The pulp sheet of the present invention may contain non-oxidized pulp in addition to the above-mentioned oxidized pulp. The non-oxidized pulp is a pulp that has not been subjected to an oxidation reaction using an oxidizing agent or the like, and is a pulp in which 98% or more of the hydroxyl groups of glucose, which is a constituent unit of the pulp, are not oxidized. The total carboxyl group content of the non-oxidized pulp is 0.10 mmol / g or less. Examples of non-oxidized pulp include the pulps listed as raw materials for oxidized pulp. Among them, at least one selected from softwood bleached kraft pulp (NBKP) and hardwood bleached kraft pulp (LBKP) is preferred. The pulp type used may be one type alone or two or more types may be used in combination. The non-oxidized pulp may be subjected to a beating treatment, and examples of the beating treatment method include the same methods as those for the oxidized pulp.

[0022] The average fiber length of the non-oxidized pulp used in combination is preferably 0.1 mm or more, more preferably 0.3 mm or more, and even more preferably 0.5 mm or more, from the viewpoint of improving wet strength, and is preferably 5.0 mm or less, more preferably 4.0 mm or less, even more preferably 3.0 mm or less, particularly preferably 2.0 mm or less, and most preferably 1.0 mm or less, from the viewpoint of ease of production. In addition, from the viewpoint of improving wet strength, the average fiber diameter of the non-oxidized pulp used in combination is preferably 10 μm or more, more preferably 12 μm or more, even more preferably 14 μm or more, and is preferably 50 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less.

[0023] In the present invention, the content of oxidized pulp relative to the total amount of pulp is preferably 65 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, from the viewpoint of improving wet strength, and may be 100 mass%, with 100 mass% being particularly preferred.

[0024] In the present invention, the pulp sheet may contain other components in addition to the oxidized pulp and the above-mentioned non-oxidized pulp. Examples of other components include internally-filled chemicals, and specific examples thereof include chemical fixing agents such as aluminum sulfate, sizing agents such as rosin, paper strength agents such as polyacrylamide and starch, freeness retention improvers such as polyamides, antifoaming agents, fillers such as clay, talc and calcium carbonate, basic dyes, acid dyes, anionic direct dyes, and cationic direct dyes. The pulp sheet of the present invention may contain a wet strength enhancer such as polyamide, polyamine, polyamide epichlorohydrin, etc., but as described above, since it contains oxidized pulp having a specific amount of surface aldehyde groups, the amount of wet strength enhancer added can be significantly reduced or sufficient wet strength can be obtained as a pulp sheet without using it. The amount of wet strength enhancer added is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.3% by mass or less, even more preferably 0.1% by mass or less, and even more preferably substantially free of the wet strength enhancer, based on the solid content of the pulp sheet. Here, the fact that the pulp sheet does not substantially contain a wet strength enhancer means that the content of the wet strength enhancer in the solid content of the pulp sheet is 0.01% by mass or less.

[0025] <Manufacturing method of pulp sheet> The pulp sheet can be obtained by papermaking a pulp slurry containing the above-mentioned oxidized pulp. The paper machine may be appropriately selected according to the purpose from among, for example, a Fourdrinier paper machine, a gap former type paper machine, a cylinder paper machine, a short wire paper machine, and the like. After papermaking, the pulp is dehydrated and dried to obtain a pulp sheet.

[0026] <Characteristics of pulp sheets> [Wet strength] The wet strength of the pulp sheet of the present invention is not particularly limited, but is evaluated by the specific wet tensile strength measured in accordance with JIS P 8135: 0998. The specific wet tensile strength is obtained by dividing the wet tensile strength by the density. The wet strength (specific wet tensile strength) of the pulp sheet of the present invention is preferably 3.0 Nm / g or more, more preferably 4.0 Nm / g or more, and even more preferably 5.0 Nm / g or more. The upper limit is not particularly limited, but from the viewpoint of ease of production, it is 20 Nm / g or less, more preferably 15 Nm / g or less.

[0027] [Dry strength] The dry strength of the pulp sheet of the present invention is not particularly limited, but is evaluated by the specific tensile strength of the pulp sheet in a dry state measured in accordance with JIS P 8113: 2006. The specific tensile strength is obtained by dividing the tensile strength by the density. The dry strength (specific tensile strength) of the pulp sheet of the present invention is preferably 30.0 Nm / g or more, more preferably 35.0 Nm / g or more, and even more preferably 40.0 Nm / g or more. The upper limit is not particularly limited, but from the viewpoint of ease of production, it is 200 Nm / g or less, more preferably 100 Nm / g or less, and even more preferably 70 Nm / g or less.

[0028] [Basic weight] The basis weight of the pulp sheet of the present invention is not particularly limited, but from the viewpoint of obtaining a pulp sheet having excellent wet strength, it is preferably 10 g / m 2 More preferably, 20 g / m 2 More preferably, 30 g / m 2More preferably, 50 g / m 2 and preferably 500 g / m 2 Less than 300 g / m 2 More preferably, 100 g / m 2 Less than 80 g / m 2 The following is the result.

[0029] 〔density〕 The density of the pulp sheet of the present invention is not particularly limited, but from the viewpoint of obtaining a pulp sheet having excellent wet strength, it is preferably 0.1 g / cm 3 More preferably, 0.2 g / cm 3 More preferably, 0.3 g / cm 3 and preferably 5 g / cm 3 Less than 3 g / cm, more preferably 3 g / cm 3 More preferably, 1 g / cm 3 The following is the result.

[0030] [Application] The pulp sheet of the present invention has excellent wet strength, and furthermore, the excellent wet strength can be obtained without adding a wet strength enhancer, and therefore, the sheet is made of pulp alone and is applicable to fields where high wet strength is required. Specifically, the pulp sheet of the present invention is expected to be used for household paper such as tissues and napkins, food packaging paper, and the like. EXAMPLES

[0031] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0032] [Production Example 1] (Preparation of oxidized pulp 1) A dried sheet of commercially available bleached hardwood kraft pulp (carboxyl group content: 0.07 mmol / g, aldehyde content: 0.03 mmol / g) was disintegrated in a disintegrator, and then diluted with ion-exchanged water to prepare a 1% pulp slurry. To the pulp slurry, 1.6 parts by mass of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), 10 parts by mass of NaBr, and 1.9 mmol of NaClO per 1 g of pulp were added per 100 parts by mass of pulp, and the mixture was left at room temperature for one hour to carry out TEMPO oxidation. The TEMPO oxidation was carried out at pH 10±0.3, and was adjusted with 1N sodium hydroxide. The reaction was terminated when the pH no longer decreased, and the mixture was filtered and washed. The pulp thus obtained was designated oxidized pulp 1. In addition, oxidized pulp 1 was diluted to 10% with ion-exchanged water, and then beaten in a PFI mill in accordance with TAPPI Test Method T248 wd-97. Beating was performed at 10,000 rpm and 20,000 rpm.

[0033] (Oxidized Pulp 2) Oxidized pulp 2 was prepared in the same manner as oxidized pulp 1, except that the amount of NaClO added was changed to 3.8 mmol per 1 g of pulp. In addition, the oxidized pulp was subjected to a beating treatment in the same manner as in the case of oxidized pulp 1.

[0034] (Non-oxidized pulp) The bleached hardwood kraft pulp before TEMPO oxidation was used as the non-oxidized pulp. The non-oxidized pulp was beaten in the same manner as the oxidized pulp 1. The properties of non-oxidized pulp, oxidized pulp 1, and oxidized pulp 2 are summarized in Table 1. The figures after "±" indicate the standard deviation (n=5).

[0035] [Measurement of pulp properties] The methods for measuring the properties of pulp are as follows. <Carboxy group content and aldehyde group content> The carboxyl group content was measured by conductometric titration. The aldehyde group content was calculated by measuring the amount of carboxyl groups after oxidation with chlorous acid in an acetate buffer solution, and then calculating the amount of carboxyl groups from the values ​​before and after oxidation. The amount of surface carboxyl groups and the amount of surface aldehyde groups on the pulp surface were measured by colloid titration. More specifically, the amount of surface carboxyl groups was measured by a particle charge meter (PCD-03, manufactured by MUTEK) using 0.025N poly-PVSK (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 0.025N poly-DADMAC (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) according to the method described in Colloid Surface A, 289 219-225 (2006). The amount of surface aldehyde groups was calculated by measuring the amount of surface carboxyl groups in the same manner after oxidizing oxidized pulp with chlorous acid under an acetate buffer solution, and calculating the amount of surface carboxyl groups before and after oxidation.

[0036] <Fiber length and diameter> Pulp length The average fiber length and average fiber diameter were measured using a Kajaani FiberLab (Metso Automation) in accordance with TAPPI Test Method T233 cm-95.

[0037] [Table 1]

[0038] The TEMPO oxidation increased the amount of carboxyl groups and aldehyde groups in the pulp compared to non-oxidized pulp. As the amount of hypochlorous acid used in the oxidation increased, the amount of carboxyl groups increased, but the amount of aldehyde groups decreased slightly. In addition, the amount of surface aldehyde groups increased significantly by beating oxidized pulp 1 and oxidized pulp 2. On the other hand, the amount of surface carboxyl groups also increased by beating, but the increase was not as significant as that of surface aldehyde groups.

[0039] Examples and Comparative Examples The non-oxidized pulp, oxidized pulp 1, or oxidized pulp 2 obtained by the above method was diluted with ion-exchanged water to make a 0.5% slurry, and then the slurry was spun into a 60 g / m2 slurry by a hand-made sheet machine. 2 The hand-made sheets were prepared using ion-exchanged water at a pressing pressure of 4.0 kgf / cm. 2 After pressing for 5 minutes at 105°C, the absorbent filter paper was replaced and the paper was pressed for another 2 minutes to dehydrate it. The pressed handsheet was then dried in a rotary drum dryer at 105°C for 2 minutes to obtain a pulp sheet. The prepared pulp sheet was conditioned overnight at 23°C and 50% humidity, after which the density, dry strength, and wet strength were measured. The results are shown in Table 2. Figure 1 shows the relationship between the amount of surface aldehyde groups and wet strength. The wet strength was measured in accordance with JIS P 8135:1996 (n=10). The dry strength was measured in accordance with JIS P 8113:2006 (n=10).

[0040] [Table 2]

[0041] The results in Table 2 and Figure 1 reveal that there is a strong correlation between the amount of surface aldehyde groups and wet strength, and that by setting the amount of surface aldehyde groups within a specific range, a pulp sheet with excellent wet strength can be obtained. [Industrial Applicability]

[0042] According to the present invention, a pulp sheet with excellent wet strength is obtained by using an oxidized pulp having a specific amount of surface aldehyde groups. The pulp sheet of the present invention is expected to be applied to various pulp sheets that require wet strength, since it can provide a pulp sheet with excellent wet strength without using a reduced amount of wet strength agent or without using a wet strength agent.

Claims

1. It is a pulp sheet containing oxidized pulp, The oxidized pulp is a pulp oxidized using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) as a catalyst; The oxidized pulp has a surface aldehyde group amount of 0.010 mmol / g or more and 0.25 mmol / g or less, The carboxy group content of the oxidized pulp is from 0.1 mmol / g to 1.7 mmol / g; The content of the oxidized pulp is 65% by mass or more of the total pulp, The basis weight of the pulp sheet is 30 g / m 2 More than 100g / m 2 is as follows: The density of the pulp sheet is 0.5 g / cm 3 or more and 1 g / cm 3 or less, The wet strength is 5.2 Nm / g or more; Pulp sheet for household paper.

2. The household paper pulp sheet according to claim 1, wherein the average fiber length of the oxidized pulp is 0.1 mm or more and 3.0 mm or less.

3. The household paper pulp sheet according to claim 1 or 2, wherein the average fiber diameter of the oxidized pulp is 10 μm or more and 50 μm or less.

4. 4. The pulp sheet for household paper according to any one of claims 1 to 3, wherein the specific tensile strength is 42.6 Nm / g or more.

Citation Information

Patent Citations

  • Fiber raw material and method for producing the same

    JP2001049591A

  • Paper using modified pulp and paper container

    JP2001336084A

  • Method for treating pulp

    JP2009228186A

  • Waterproof paper

    JP2016089306A

  • Pulp slurry and pulp sheet

    JP2016223042A